Daiktavardžio junginiai su bendratimi lietuvių ir anglų kalbose - Tekorienė, D. (Kalbotyra, 1977)
The contrastive study of the syntactic constructions “noun + infinitive” in Lithuanian and English is based on textua1 equivalence. The aims of the paper are: 1. to determine which Lithuanian and English constructions “noun+infinitive” exhibit contextual equivalence; 2. to study the equivalent constructions in terms of formal and functional equivalence; 3. to ascertain whether English possesses any collocations textually equivalent to, yet formally different from Lithuanian collocations “noun + infinitive”. The answers to problems one and two are obtained through investigation of the semantic classes of nouns capable of collocating with the Infinitive in Lithuanian and English as well as through the study of semantic and syntactic relations of the formatives within and outside the collocation. The study of the third problem is reduced to the study of English synonymous constructions of three types “noun + infinitive”, “noun + gerund”, “noun + preposition + noun”.